VD_FINDINFO HC / 2011 / 611 vom 31. Oktober 2011 - VD Tribunal cantonal (2011)
MESURE DE CONTRAINTEDROIT DES ÉTRANGERS, DÉTENTION AUX FINS D'EXPULSION | 76 al. 1 LEtr, 76 al. 2 LEtr, 76 al. 3 LEtr, 76 al. 4 LEtr, 79 LEtr, 80 LEtr, 20 LVLEtr, 30 LVLEtr